Pengaruh Pendidikan Kesehatan Melalui Media Booklet Terhadap Pengetahuan dan Sikap PPIA Pada Ibu Hamil - Anis Nikmatul Nikmah; Meirna Eka Fitriasnani; Lindha Sri Kusumawati; Fithri Rifatul Himmah (WOMB Midwifery Journal, 2024)
PPIA (Prevention of HIV-Transmission from Mother to Child) is one of the efforts to control HIV-AIDS and STIs in pregnant women. Data from Kediri City in 2023, from the target of 263 pregnant women, 248 people checked PPIA and there was 1 pregnant woman who was HIV positive. The low coverage of pregnant women is forced to do an examination because this is a mandatory program that must be done. The purpose of this study was to determine the Effect of Health Education through Booklet Media on PPIA Knowledge and Attitudes in Pregnant Women. This research method is a pre-experimental, one group pretest-postest design design. Population of all pregnant women who visited the health center with the number of invinite. The research sample was 30 respondents. Sampling technique with Acidental Sampling. Research location at Puskemas Ngletih Kediri City in January 2024 Data collection through questionnaires to obtain primary data. Test research analysis with Wilcoxon test. The results showed that after being counseled, most of the knowledge was sufficient by 16 respondents (53.3%) and most of the attitudes were positive by 22 respondents (73.3%). Based on the Wilcoxon test on knowledge obtained PValue 0.000<α 0.05) while in the attitude P Value 0.012<α 0.05 which means H0 is rejected and H1 is accepted. From the results of the study, it was concluded that there is an influence of health education through booklet media on the knowledge and attitudes of PPIA in pregnant women. Health workers are expected to always strive to provide socialization and motivation to pregnant women so that the knowledge and attitudes of pregnant women about PPIA prevention will increase.